Association Between Asymptomatic Vulnerable Carotid Plaques and Cognitive Impairment in Rural Adults - Zhang, Jia; Wang, Zixuan; Zhou, Mingyue; Jia, Jiaokun; Liu, Yanfang; Wang, Anxin; Guo, Mengyi; Chen, Shengyun; Zhao, Xingquan (Frontiers in Neurology, 2020)
Background: The prevalence of cognitive impairment is growing and higher in rural areas. The association between carotid plaque and cognitive impairment remains uncertain, and few studies focused on the cognitive function of the rural population. We designed this study to investigate the association between carotid plaque and cognitive impairment in a rural community. Methods: We enrolled 3336 participants who underwent carotid ultrasound and cognitive function measurements, free of cerebrovascular diseases, and without neurological deficits, from the China National Stroke Screen Survey program. Cognitive function was evaluated by the Montreal Cognitive Assessment (Beijing version). We used multivariable logistic regression to assess the association between asymptomatic carotid plaques and the presence of cognitive impairment. Results: Nine hundred seventy-six participants had cognitive impairment in this study. After adjustment for potential confounding factors, asymptomatic carotid plaques (odds ratio was 1.35; 95% confidence interval, 1.15-1.58), especially vulnerable carotid plaques (odds ratio was 1.54; 95% confidence interval, 1.28-1.85), were associated with cognitive impairment. Conclusion: In this community-based and observational study, asymptomatic vulnerable carotid plaque is an independent and significant risk factor for cognitive impairment in rural residents.